Characteristics of Beach Seine Fishery of East Java: Facing Ministerial Decree of Marine Affairs and Fisheries No. 2/2015 - Dewa Gede Raka Wiadnya; Budy Wiryawan; Marsoedi Marsoedi; Wahyu Endra Kusuma; Arief Darmawan (Research Journal of Life Science, 2017)
Catch biomass and time-trend perception of Beach seine fishery were studied during 2015, from four different sites in East Java: Padikde Madura, Santan Island Banyuwangi, Prigi Beach Trenggalek, and Dangkal Beach Pacitan. The study aimed to assess the impact of recently Ministerial Decree (No. 2/2015) on this particular fishery. Catch biomass was analyzed based on swept area method. Time trend perception was traced back from fishermen in relation to reduced catch biomass, catch size, habitat degradation, and income contribution from the fishery. The results showed that Beach Seines in East Java are considerably subsistence. It swept fixed-bottom habitats of 1–9 ha. Average catch biomass for all sites was 15±19.4 kg trip-1. With low price of fish catch, fishermen cannot place down their family income solely from this livelihood. Beach seine is more as to maintain tradition of subsistence. Fishermen clearly observed the reduced in catch biomass and catch size compared to what it used to be (±30 years ago). With very low contribution to total catch in the region, negligible impact to habitat degradation, and consumed no fuel subsidy, it is no real reason to include this gear in general ban through Ministerial Decree of Marine Affairs and Fisheries.